Retweet or reply? Covid-19 and Twitter. The case of the city of Bahía Blanca (Argentina) - Gutiérrez, Emiliano; Meller, Leandro; Virdis, Juan Marcelo; De Simón, Federico; Gurovich, Carlos; Fernández Leyes, Lucas (AWARI, 2020)
The unprecedented global context caused by COVID-19 has generated various changes in society and forced the governments of different countries to adopt containment measures. However, this crisis occurs in a globalized international context, where the mass use of various digital platforms allows the generation of a significant amount of information and the study of interactions between individuals. In this work, in particular, the impact on public opinion about the coronavirus crisis in the city of Bahía Blanca (Argentina) is analyzed from the Twitter digital platform, trying to identify the main actors in the production of messages, find out which users having a greater capacity to control its diffusion and measure the relevance or authority in the interactions analyzed using Social Network Analysis techniques. The main result is the fragmentation of information between individuals, being the resulting interaction scarce. On the other hand, it was found that in the analysis of retweets the main actors are not relevant outside the digital platform, while in the analysis of the responses the main actors are characterized by having a prominent role in the political scene or in communications locally.